Water Quality Characteristics of a Water Hyacinth Infested Tropical Highland Lake: Lake Tana, Ethiopia - Dersseh, Minychl G.; Steenhuis, Tammo S.; Kibret, Aron A.; Eneyew, Bantesew M.; Kebedew, Mebrahtom G.; Zimale, Fasikaw A.; Worqlul, Abeyou W.; Moges, Mamaru A.; Abebe, Wubneh B.; Mhiret, Demesew A.; Melesse, Assefa M.; Tilahun, Seifu A. (Frontiers in Water, 2022)
Nutrient enrichment from increased anthropogenic activities has been associated with algal blooms and the proliferation of aquatic weeds such as water hyacinth. It is a recent phenomenon in developing nations in the tropical monsoon regions where the link between water quality parameters and water hyacinth infestation is unclear. This study investigates the relationship between phosphorus, nitrogen and chlorophyll-a on the distribution of water hyacinths in Lake Tana located in the tropical highlands of Ethiopia. In this 3,000 km2 lake, water hyacinths have expanded from almost none to 25 km2 during the last ten years. Water samples were taken at 27 nearshore stations with different levels of water hyacinth infestation at 0.5 m depth and the lake bottom. In addition, samples were taken near the river mouths to calculate the total nutrient loading of the rivers. Samples were analyzed for total phosphorus, total nitrogen and chlorophyll-a. The results show that water hyacinths were found mainly in the Northeast part of Lake Tana. At the same time, the total phosphorus and nitrogen concentrations were suitable for the growth of water hyacinths throughout the lake. Infested areas had total phosphorus concentrations of over 2 mg/l compared to less than 1 mg/l elsewhere and total nitrogen concentrations were over 2 mg/l at locations with water hyacinths and less for shore areas without water hyacinths. Chlorophyll-a was found in the range of 0.3-104.2 µg/l and minimum values of Chl-a was related to the location of the water hyacinths. The expansion of water hyacinth in Lake Tana can be managed by identifying and addressing the sources of nutrients from the catchment.